Mechanical Strength Investigation of Gyroid Design Parameters in Titanium Fixed Partial Denture Frameworks Manufactured by Additive Manufacturing - Çalışkan, Cemal İrfan; Khan, Hamaid Mahmood; Koca, Aliihsan; Şahin, Meryem; Tarakçı, Gürkan; Sivri, Burak (Springer, 2024)
Additive manufacturing (AM) has emerged as a highly effective method within the biomedical field, particularly in prosthetic applications, where it offers numerous advantages such as reduced weight and improved user comfort. This study investigates how modifications to gyroid design parameters influence the mechanical strength of denture frameworks produced via additive manufacturing. Employing a multidisciplinary approach, the research encompasses several key stages: redesigning data from tomography scans, fabricating samples with titanium using additive manufacturing, conducting compression tests, and analyzing the samples through scanning electron microscopy (SEM) in a metallography laboratory. The investigation also includes fracture analysis and finite element analysis (FEA) to assess performance. By adopting gyroid geometry in framework designs, this study presents a novel method that enhances mechanical strength while significantly decreasing weight. Findings indicate that the integration of gyroid structures can maintain equivalent mechanical strength compared to traditional designs while achieving material savings of up to 40%.
Keywords: Additive manufacturing (AM); Laser powder bed fusion; Gyroid; Design for AM (DfAM); Titanium framework